Implementasi Lab Virtual berbasis Teknologi Kontainer Multi Klaster dengan Orkestrator Kubernetes - Mohammad Zulfikar; Adhitya Bhawiyuga; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In field of information technology education, provisioning virtual lab is very important to provide practical experience to learners. This has made many universities develop their own virtual labs. However, in practice, each university can have limited or excess of resources. This makes the existing virtual lab run inefficiently. This research proposes the implementation of virtual lab based on multi-cluster container technology with Kubernetes orchestrator to create virtual lab system that allows universities to share resources. The implementation of the virtual lab system is carried out by implementing three main components: orchestrator cluster, university cluster, the Rancher multi-cluster management platform as the university cluster controller. The functional evaluation results in adding new university clusters, displaying university clusters information, running container applications, exposing application within the cluster to outside of the cluster, adding new users, managing access rights of these users, and manages the resource usage of the running container are all well-functioning. The non-functional test results shows that the system can handle requests from 1000 users simultaneously with 32.84% CPU and 77.60% Memory utilization. Meanwhile, when handling 10000 users, the system can handle 79.5% of the total requests with 83.18% CPU and 77.06% Memory utilization. From the test results, the system in this study is proven to have good scalability to handle access by many learners and can be a solution for a container-based virtual lab system.